Stone tools in the Paleolithic and Neolithic near East a guide - Shea, John J. (Cambridge University Press, 2013)
Stone Tools in the Paleolithic and Neolithic Near East: A Guide surveys the lithic record for the East Mediterranean Levant (Lebanon, Syria, Israel, Jordan, and adjacent territories) from the earliest times to 6,500 years ago. It is intended both as an introduction to this lithic evidence for students and as a resource for researchers working with Paleolithic and Neolithic stone tool evidence. Written by a lithic analyst and professional flintknapper, this book systematically examines variation in technology, typology, and industries for the Lower, Middle, and Upper Paleolithic; the Epipaleolithic; and Neolithic periods in the Near East. It is extensively illustrated with drawings of stone tools. In addition to surveying the lithic evidence, the book also considers ways in which archaeological treatment of this evidence could be changed to make it more relevant to major issues in human origins research. A final chapter shows how change in stone tool designs points to increasing human dependence on stone tools across the long sweep of Stone Age prehistory
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Funde; Paleolithic period / Middle East; Neolithic period / Middle East; Tools, Prehistoric / Middle East; Stone implements / Middle East; Ausgrabung; Neolithikum; Paläolithikum; Steingerät; Naher Osten; Middle East / Antiquities